The sweating response of elite professional soccer players to training in the heat - Shirreffs, S. M.; Aragon-Vargas, L. F.; Chamorro, M.; Maughan, R. J.; Serratosa, L.; Zachwieja, J. J. (International Journal of Sports Medicine, 2005)
Sweat rate and sweat composition vary extensively between individuals, and quantification of these losses has a role to play in the individualisation of a hydration strategy to optimise training and competitive performance. Data were collected from 26 male professional football (soccer) players during one 90 min pre-season training session. This was the 2nd training session of the day, carried out between 19.30 and 21.00 h when the mean ± SD environment was 32 ± 3 °C, 20 ± 5 %rh and WBGT 22 ± 2°C. Training consisted of interval running and 6-a-side games during which the average heart rate was 136 ± 7 bpm with a maximum rate of 178 ± 7 bpm (n = 19). Before and after training all players were weighed nude. During training all players had free access to sports drinks (Gatorade®) and mineral water (Solan de Cabras®). All drink bottles were weighed before and after training. Players were instructed to drink only from their own bottles and not to spit out any drink. No player urinated during the training session. Sweat was collected by patches from the chest, arm, back, and thigh of a subgroup of 7 players. These remained in place for the first 15 - 30 min of the training session, and sweat was analysed for sodium (Na+) and potassium (K+) concentration. Body mass loss was 1.23 ± 0.50 kg (ranging from 0.50 to 2.55 kg), equivalent to dehydration of 1.59 ± 0.61 % of pre-training body mass. The sweat volume lost was 2193 ± 365 ml (1672 to 3138 ml), but only 972 ± 335 ml (239 to 1724 ml) of fluid was consumed. 45 ± 16 % of the sweat volume loss was replaced, but this ranged from 9 % to 73 %. The Na+ concentration of the subgroup's sweat was 30.2 ± 18.8 mmol/l (15.5 to 66.3 mmol/l) and Na+ losses averaged 67 ± 37 mmol (26 to 129 mmol). The K+ concentration of the sweat was 3.58 ± 0.56 mmol/l (2.96 to 4.50 mmol/l) and K+ losses averaged 8 ± 2 mmol (5 to 12 mmol). The drinking employed by these players meant that only 23 ± 21 % of the sweat Na+ losses were replaced: This ranged from replacing virtually none (when water was the only drink) to replacing 62 % when the sports drink was consumed. These elite soccer players did not drink sufficient volume to replace their sweat loss. This, however, is in accord with data in the literature from other levels of soccer players and athletes in other events. These measurements allow for an individualisation of the club's hydration strategy.